Social trauma and the mu-opioid system in depression - Malcolm-Smith, Susan (Department of Psychology, 2015)
The overarching thesis under investigation is that the endogenous opioid system plays a key role in depression subsequent to traumatic childhood social experiences. This is suggested by the fact that animal work indicates that mu-opioids robustly mediate separation-distress, and that early social stressors lead to long term dysregulation in key related circuitries and neuroanatomical structures.